2015
DOI: 10.1016/j.toxrep.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat exposure induces behavioral deficits in larval zebrafish during the window of dopamine neurogenesis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…Moreover, paraquat had only mild effects, if any, on locomotion. Some reports document a near 3-fold difference in total distance [26], while others did not see the same deficit [10]. Contrarily to Bretaud et al we found notable morphological defects in zebrafish treated with paraquat alone.…”
Section: Paraquatsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, paraquat had only mild effects, if any, on locomotion. Some reports document a near 3-fold difference in total distance [26], while others did not see the same deficit [10]. Contrarily to Bretaud et al we found notable morphological defects in zebrafish treated with paraquat alone.…”
Section: Paraquatsupporting
confidence: 69%
“…However, exposure to paraquat has been shown to yield inconsistent reports in the literature. This is particularly evident in zebrafish studies, where some have outlined a severe neurodegenerative impact of paraquat on dopamine and serotonin protein levels [25,26], while others observed no obvious phenotypes [10]. This variable effect extends to behavioral symptoms following treatment, where some groups observed significant motor impairment [27], while others report no fluctuations in any swimming activity parameter [10].…”
Section: Introductionmentioning
confidence: 98%
“…In this study, zebrafish embryos with body curvature have been identified in both 3 hpf and 24 hpf groups after treatment with KH. According to Nellore and Nandita (2015), curved spine (body curvature) is a type of neurodegenerative phenotype that is associated with central nervous system (CNS) development. Floor plate is a specialized stripe of large cuboidal structure in the ventral neural tube of CNS (Brand et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish larval behaviour was previously shown to be affected after exposure to various toxicants at the early embryonic stages (Nellore, 2015;Fraser et al, 2017). Here, behavioural changes resulting from a short duration early life exposure to UV were assessed 5 days post fertilization, and results showed that exposure to the two highest UVA doses resulted in a significant decrease in larval activity compared to the controls.…”
Section: Behaviourmentioning
confidence: 92%
“…Changes in behaviour may represent either compensatory and reversible adaptive responses in order to mitigate potential overt effects after perception of stress), such as reported in Atlantic cod after sea temperature changes (Alemanni et al, 2003;Freitas et al, 2015). They also may be irreversible effects of a toxicant on a behavioural mechanism or expression after toxicokinetic and toxicodynamic processes have started (Nellore, 2015) and are found to be an indicator of overall welfare (Martins et al, 2012). Some claim that behavioural changes might be pointing to neurodevelopmental toxicity of studied agents (Levin and Cerutti, 2009;Rihel and Schier, 2012).…”
Section: Behaviourmentioning
confidence: 98%